The ICD-10 Classification of Mental and Behavioural Disorders : Clinical Descriptions and Diagnostic Guidelines. - Organization, World Health (Guidelines on Construction of Core Indicators., 1992)
Clinical descriptions, diagnostic guidelines and codes for mental and behavioural disorders encountered in clinical psychiatry. The book has been developed from chapter V of the 10th revision of "The International Statistical Classification of Diseases and Related Health Problems (ICD-10).